Penerapan Pegaruh Mobilisasi Dini Terhadap Peristaltik Usus Pada Asuhan Keperawatan Pasien Dengan Post Op Laparatomi - Saputra, Dikki; Kesuma Intani, Merlisa; Litaqia, Wulida; Prawira, Ricky (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Postoperative paralytic ileus is a common complication following laparotomy, characterized by a temporary cessation of bowel motility, leading to discomfort, delayed recovery, and prolonged hospital stay. Risk factors include surgical complexity, perioperative complications, preoperative conditions, and suboptimal postoperative management. Early mobilization has been proven to accelerate the recovery of gastrointestinal function by enhancing bowel peristalsis, reducing complications, and expediting patient recovery. This study employs a case study method on a postoperative laparotomy patient experiencing decreased bowel peristalsis. Early mobilization interventions were conducted from July 20 to 22, 2024, on one postoperative laparotomy patient in the surgical inpatient ward of Hospital X. The intervention included position changes, sitting, and standing with assistance. Evaluation was carried out by measuring bowel sounds frequency before and after the intervention. The results showed an increase in bowel peristalsis from 3 times per minute to 18 times per minute after early mobilization on the third day. Early mobilization plays a crucial role in accelerating postoperative recovery by enhancing bowel peristalsis and reducing complications. The implementation of this intervention requires a structured approach, including activity monitoring and appropriate rehabilitation. This study reaffirms the importance of early mobilization as an effective strategy to expedite recovery in postoperative laparotomy patients.